Level kesegaran jasmani siswa kelas lima SD Negeri 1 dan 41 Kaur Selatan - Febrianto, Agung Pratama (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
The physical fitness of students is influenced by the daily activities of students both within and outside the school. The physical fitness of students can affect the patterns of student sports activities at school. This study aims to determine the level of physical fitness of grade V SD Negeri 1 and 41 in South Kaur. The method used in this research is descriptive quantitative research method. The population in this study were students of class V SD Negeri 1 and 41 in South Kaur. While the sample in this study were 44 students consisting of 26 female students and 18 male students. The instruments in this study were Indonesian physical fitness tests and Arsil's theory (2010). The results of this study found that the physical fitness level of the fifth-grade students of SD Negeri 1 and 41 in South Kaur was in the poor category because it had the highest percentage, namely 70%.